An Empirical Analysis of Investor Confidence Incorporated in Market Prices. Issue 3 (3rd July 2019) - Murphy, Austin; Fu, Liang
Abstract: Using market prices for an equity index, this research empirically estimates the complex interrelationship between the confidence of informed investors, aggregate market sentiment, and many other variables. The empirical results uncover new insights on investment behavior, including novel evidence on the root causes of various financial phenomena like the momentum and calendar month effects, which themselves appear to be caused by the incentive systems existing among institutional investors. Investor confidence is found to fall (rise) with moderate (large) deviations between market prices and intrinsic values, but only true knowledge of that variable is discovered to enhance investment returns.